Balancing selection, genetic drift, and human‐mediated introgression interplay to shape MHC (functional) diversity in Mediterranean brown trout - Lorenzo Talarico; Silvio Marta; Anna Rita Rossi; Simone Crescenzo; Gerardo Petrosino; Marco Martinoli; Lorenzo Tancioni (Ecology and Evolution, 2021)
Abstract The extraordinary polymorphism of major histocompatibility complex (MHC) genes is considered a paradigm of pathogen‐mediated balancing selection, although empirical evidence is still scarce. Furthermore, the relative contribution of balancing selection to shape MHC population structure and diversity, compared to that of neutral forces, as well as its interaction with other evolutionary processes such as hybridization, remains largely unclear. To investigate these issues, we analyzed adaptive (MHC‐DAB gene) and neutral (11 microsatellite loci) variation in 156 brown trout (Salmo trutta complex) from six wild populations in central Italy exposed to introgression from domestic hatchery lineages (assessed with the LDH gene). MHC diversity and structuring correlated with those at microsatellites, indicating the substantial role of neutral forces. However, individuals carrying locally rare MHC alleles/supertypes were in better body condition (a proxy of individual fitness/parasite load) regardless of the zygosity status and degree of sequence dissimilarity of MHC, hence supporting balancing selection under rare allele advantage, but not heterozygote advantage or divergent allele advantage. The association between specific MHC supertypes and body condition confirmed in part this finding. Across populations, MHC allelic richness increased with increasing admixture between native and domestic lineages, indicating introgression as a source of MHC variation. Furthermore, introgression across populations appeared more pronounced for MHC than microsatellites, possibly because initially rare MHC variants are expected to introgress more readily under rare allele advantage. Providing evidence for the complex interplay among neutral evolutionary forces, balancing selection, and human‐mediated introgression in shaping the pattern of MHC (functional) variation, our findings contribute to a deeper understanding of the evolution of MHC genes in wild populations exposed to anthropogenic disturbance.